Does obesity-associated insulin resistance affect brain structure and function of adolescents differentially by sex?. (January 2022) - Gabay, Andrea; London, Stephanie; Yates, Kathy F.; Convit, Antonio
Highlights: Degree of IR is associated with brain and cognitive variables differentially by sex. In female adolescents, IR may play a role in negative effects on frontal lobe brain structures, such decreased thickness in the ACC, OFC, and insula cortex. In female adolescents, degree of IR is also associated with executive function tasks such as stroop and digit symbol substitution (DSST) tests. Abstract: Metabolic abnormalities affect the adolescent brain. For equivalent abnormalities in metabolism young people exhibit deficits in more cognitive domains than adults. We examine sex differences performance for adolescents with obesity/insulin resistance (IR) and evaluated how sex and IR effected frontal lobe structures and executive functioning. 125 adolescents underwent medical, cognitive, and brain-imaging assessments. Participants were categorized as insulin sensitive (IS) (QUICKI ≥ 0.350) or IR (QUICKI < 0.350). Degree of IR may affect brain and cognition differentially by sex. Females had positive associations between QUICKI and anterior cingulate cortex (ACC) volume, medial orbito-frontal cortex (OFC) thickness, and scores on the Stroop and Digit Symbol Substitution (DSST) tests. Females with IR tended to have thinner insular cortices. No such associations were found in males. In female adolescents, IR may negatively affect brain structure and function. No such effects were found for males. Although needing more development, hormonal effects and inflammation are potential contributors.